Metody hodnocení pro management rizik ve veřejné správě - Kořínek, Tomáš (Univerzita Pardubice, 2010)
The aim of the article is to describe the current state of methods used for risk assessment in public administration, which are an important part of the Risk Managemet. The article also described in more detail the original index method, which, unlike the other mentioned methods, allows comparison of risk levels of individual spheres of regional life and mutual comparison of the overall security in regions.
Keywords: original index method; public administration; risk assessment; risk management; uncertainty